2019
DOI: 10.4236/jbm.2019.77004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dyslipidemia and Assessment of Atherogenic Risk amongst Cameroonian Living in Yaounde: A Cross Sectional Study

Abstract: Background: This study was conducted to evaluate the lipid profile in nutritional categories, to characterize dyslipidemia and assess cardiovascular risk, to describe association between anthropometric markers, incidence of dyslipidemia and cardiovascular risk in Cameroonian adults. Methods: A cross-sectional survey was conducted in Yaoundé from April 2014-June 2015. It included 1986 individuals, aged 20-65 years, both males (30.7%) and females (69.3%). Blood pressure, anthropometric measurement including weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…This Journal of Biosciences and Medicines assumption is supported by some of our previous studies where we found that 49% of WCBA had low/moderate physical activity, 50% rarely or occasionally consumed fruits/vegetables and 60% were obese [20]. This result is in line with that reported in several Asian countries [37] [38] [39]. Women under cancer therapy had and HDL-c levels, and this suggests a role of cancer therapy in appearance of dyslipidaemia as reported earlier with taxanes-containing chemotherapies [40] [41] [42].…”
Section: Discussionsupporting
confidence: 90%
“…This Journal of Biosciences and Medicines assumption is supported by some of our previous studies where we found that 49% of WCBA had low/moderate physical activity, 50% rarely or occasionally consumed fruits/vegetables and 60% were obese [20]. This result is in line with that reported in several Asian countries [37] [38] [39]. Women under cancer therapy had and HDL-c levels, and this suggests a role of cancer therapy in appearance of dyslipidaemia as reported earlier with taxanes-containing chemotherapies [40] [41] [42].…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated that menopausal status was not significantly associated with serum lipid level which contradicts from studies conducted in India that reported TC, TG, and LDL-c were significantly higher on postmenopausal women than Pre-menopausal women. 36 A recent study conducted in Cameroon revealed that significantly high TC, LDL-c, TG, and lower HDL-c were observed among obese women participants as compared to normal weight. 36 This study showed no significant association between serum lipid level and breast cancer risks like the habit of smoking, low physical activity, early menarche, history of abortion, contraceptive use.…”
Section: Discussionmentioning
confidence: 98%
“… 36 A recent study conducted in Cameroon revealed that significantly high TC, LDL-c, TG, and lower HDL-c were observed among obese women participants as compared to normal weight. 36 This study showed no significant association between serum lipid level and breast cancer risks like the habit of smoking, low physical activity, early menarche, history of abortion, contraceptive use. It contradicts from studies in Paris that reported a significant association between higher serum TG and menopausal status and India which reported significant association between high serum TC, TG and LDL-c and low HDL-c level and BMI.…”
Section: Discussionmentioning
confidence: 98%
“…Así mismo Col No HDL-c y TG/HDL-c resultaron ser los más prevalentes en adultos venezolanos en un estudio realizado por García 30 , encontrándose de esta manera resultados variables. Los índices aterogénicos LDL-c/HDL-c; Colesterol Total/HDL-c y TG/HDL-c son relaciones matemáticas de marcadores lipídicos fuertemente asociados para incrementar el riesgo de enfermedades cardiovasculares 31 y riesgo de mortalidad 32 debido probablemente en su relación con el grosor de la media e íntima de las arterias carótida y arteria coronaria en la evaluación de un proceso aterogénico 33 aspecto importante a considerar para la prevención y/o tratamiento de su desarrollo.…”
Section: Resultsunclassified